2007
DOI: 10.1001/archinte.167.10.1083
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Abnormalities at the Onset of Treatment of End-Stage Renal Disease

Abstract: Background: Laboratory abnormalities at the start of treatment of end-stage renal disease (ESRD) have been reported as worse in racial/ethnic minorities than in white patients, suggesting racial disparities in care. It is not known whether these differences are attributable to racial/ ethnic differences in socioeconomic status (SES). Methods: We tested associations between race/ ethnicity, SES, and type of medical insurance and serum creatinine level, estimated glomerular filtration rate, serum albumin level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Socially deprived patients in the US have lower hemoglobin (Hb) (3) and lower rates of erythropoietin (EPO) use at the start of RRT (4). Once on dialysis in the US, Blacks tend to achieve lower Hb levels (5), lower dialysis dose (5), and higher parathyroid hormone (PTH) levels (6) than Whites, whereas patients of South Asian descent achieve Hb levels comparable to those of Whites and a higher dialysis dose (7).…”
mentioning
confidence: 99%
“…Socially deprived patients in the US have lower hemoglobin (Hb) (3) and lower rates of erythropoietin (EPO) use at the start of RRT (4). Once on dialysis in the US, Blacks tend to achieve lower Hb levels (5), lower dialysis dose (5), and higher parathyroid hormone (PTH) levels (6) than Whites, whereas patients of South Asian descent achieve Hb levels comparable to those of Whites and a higher dialysis dose (7).…”
mentioning
confidence: 99%
“…Multiple USRDS reports using Form 2728 data have concluded that ongoing levels of suboptimal degrees of anemia in incident patients with ESRD are in part because of underuse of ESA [17] review articles, which relied on Form 2728 data, have also found that less than one-third of patients with incident dialysis received predialysis ESA and that those with lower hemoglobin values were even less likely to have received predialysis ESA [6][7][8][9][10][15][16]19]. Only one group of investigators expressed concern about predialysis ESA data misclassification on Form 2728, but doubted it was significant because an inverse correlation was found between ESA use and low hemoglobin (r = -0.65, p = 0.004) [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…CMS dialysis networks across the United States also use data from this source to assess quality of predialysis and dialysis care and to target quality improvement initiatives. Furthermore, researchers have used information from Form 2728 in a large number of clinical, epidemiological, and health services research studies [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Moreover, uninsured persons and Medicaid enrollees are suboptimally prepared for ESRD, as evidenced by worse biochemical abnormalities at ESRD onset, lower prevalence of permanent vascular access at dialysis initiation, and marked delays in accessing a kidney transplant compared with counterparts with Medicare or private health insurance. [10][11][12][13] A major contributor to socioeconomic disparities in ESRD incidence and CKD care is the lack of a surveillance system for tracking the care of the poor or …”
mentioning
confidence: 99%